Effect of Plant Densities on Biomass Production of Fast Growing Tree Species in Konkan Region, Maharashtra - Shinde, A.K.; Jadhav, B.B.; Khadtar, B.S.; Shinde, B.D.; Jambhale, A.S.; Thaware, B.L. (Indian Journal of Agroforestry, 2020)
Field experiment was conducted to evaluate the effect of different plant densities of three fast growing tree species for biomass production. The Acacia auriculiformis, Casuarina equisetifolia and Leucaena leucocephala were planted in June, 1988 at 1x1, 2x1 and 2x2 meter spacing for maximum biomass production. The pooled data for three years (after 17 years of planting) revealed that there was significant difference in height, DBH and biomass. The maximum biomass/ha was recorded in Acacia auriculiformis at 1x1 m spacing (347.1 t/ha) followed by Casuarina equisetifolia at 1x1 m spacing (318.2 t/ha). The maximum gross return (per ha per year) was recorded in Acacia auriculiformis (Rs. 33,567) and Casuarina equisetifolia (Rs. 32,343) planted at 1x1 m spacing.